DETERMINATION OF MANY-BODY EFFECT OF [Co(NH3)n]2+ (n=1-6) COMPLEXES BASE ON AB INITIO CALCULATIONS - Harno Dwi Pranowo; Karna Wijaya; Bambang Setiaji; Rhano Setyan Janu (Universitas Gadjah Mada, 2002)
The computational chemistry calculation to determine the stabilization energy and ligand-ligand repulsion energies of [Co(NH3)n]2+ system was done by using LANL2DZ basis set for Co2+ and 6-31G* basis set for NH3 at the level theory of unrestricted Hartree-Fock (UHF). Result from the calculation shows that the larger number of NH3 ligand present in the complex give the effect of the lower average binding energy per ligand molecule, i.e. -503,29 kJ/mol for [Co(NH3)]2+ and then decrease to -338,025 kJ/mol for octahedral [Co(NH3)6]2+ complex. A correlation between the number of ligand and the metal ion-ligand bond distance was studied. The result shows that the metal ion-ligand bond distance increases along with the larger number of the ligand. The calculation of average pair interaction energies between Co2+ and NH3 in [Co(NH3)n]2+ complexes were done in order to determine the error possibility caused by the neglect of non-additivity contribution. The results indicate that the maximum relative error with respect to the pair potential, %ΔEavpi, is 17,64 % [Co(NH3)6]2+ complex.